First-in-class inhibitor of HSP110 blocks BCR activation through SYK phosphorylation in diffuse large B-cell lymphoma - Gibouin, Vincent Cabaud; Durand, Manon; Boudesco, Christophe; Hermetet, François; Nozickova, Kristyna; Chassagne-Clement, Catherine; Abdelwahed, Mayssa; Klener, Pavel; Garrido, Carmen; Jego, Gaëtan (Leukemia, 2024)
Activated B-cell-like diffuse large B-cell lymphoma (ABC-DLBCL) is driven by aberrant activation of the B-cell receptor (BCR) and the TLR/MyD88 signaling pathways. The heat-shock protein HSP110 is a candidate for their regulation as it stabilizes MyD88. However, its role in overall BCR signaling remains unknown. Here, we used first-in-class HSP110 inhibitors to address this question. HSP110 inhibitors decreased the survival of several ABC-DLBCL cell lines in vitro and in vivo, and reduced the phosphorylation of BCR signaling kinases, including BTK and SYK. We identified an interaction between HSP110 and SYK and demonstrated that HSP110 promotes SYK phosphorylation. Finally, the combination of the HSP110 inhibitor with the PI3K inhibitor copanlisib decreases SYK/BTK and AKT phosphorylation synergistically, leading to suppression of tumor growth in cell line xenografts and strong reduction in patient-derived xenografts. In conclusion, by regulating the BCR/TLR signaling pathway, HSP110 inhibitors are potential drug candidates for ABC-DLBCL patients.
Keywords: nádorové buňky kultivované; kinasa Syk; Quinazolines; difúzní velkobuněčný B-lymfom; signální transdukce; zvířata; Signal Transduction; proteiny tepelného šoku HSP110; Phosphorylation; Animals; lidé; Syk Kinase; xenogenní modely - testy protinádorové aktivity; Tumor Cells, Cultured; chinazoliny; Mice; Lymphoma, Large B-Cell, Diffuse; Mice, SCID; Humans; HSP110 Heat-Shock Proteins; myši; nádorové buněčné linie; receptory antigenů B-buněk; fosforylace; myši SCID; pyrimidiny; Pyrimidines; Xenograft Model Antitumor Assays; Receptors, Antigen, B-Cell; Cell Line, Tumor